A Study on the Implementation of a Monitoring System to Solar-Powered Houses - Ignacio, Aris; Soria, Carmichael D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study involves the implementation of a solar power monitoring system to solar-powered houses to help owners keep watch and make preventive maintenances to respective solar power systems installed at home.